EFFICACY OF ZINC AS AN ANTIBACTERIAL AGENT AGAINST ENTERIC BACTERIAL PATHOGENS - Faiz, Umaira; Butt, Tariq; Satti, Luqman; Hussain, Wajid; Hanif, Faisal (Journal of Ayub Medical College Abbottabad, 2011)
Background: Diarrhoea is a serious threat all over the world with great economic implications especially evident in the developing world. This study was aimed at determining in vitro efficacy of Zinc (Zn) against common enteric bacterial pathogens. Method: A total of 100 bacterial enteric pathogens: Salmonellae (n=16), enteropathogenic Escherichia coli (EPEC) (n=26), Shigellae (n=28) and Vibrio cholerae (n=30) were isolated from diarrhoeal stool specimens at Department of Microbiology, Armed Forces Institute of Pathology Rawalpindi during Aapril 2009 to Jan 2010. These isolates were tested against various concentrations of Zn supplemented in Mueller Hinton (MH) agar using a multipoint inoculator. A minimum inhibitory concentration of active Zn in ZnSO4.7H2O ranging from 0.03 mg/ml to 1 mg/ml was used. Results: Zn completely inhibited the growth of all the tested pathogens and most of them were inhibited at a concentration of 0.06 mg/ml to 0.5 mg/ml of Zn. Conclusions: Zinc has an excellent antibacterial activity against enteric bacterial pathogens common in our setup which may provide basis for treatment of diarrhoea. Clinical study based on these findings is recommended. Keywords: Diarrhoea, zinc, antibacterial, Enteric Pathogens, Cholera, Salmonella, E. coli, Shigella